PROBLEMS AND PROSPECTS OF THE DEVELOPMENT OF DIGITALIZATION: INTERNATIONAL AND NATIONAL LEVEL - Poliakova Yuliia; Stepanov Andriy; Kostenko Anatolii; Krutiak Mariia (Львівський торговельно-економічний університет, 2023)
The article is concerned with studying the role of digitalisation processes in the economic development of countries in the context of new modern challenges. The general scientific approaches to the definition of the concept of "digitalisation" in economic activities are highlighted. The role of modern digital technologies in achieving the competitiveness of enterprises, industries, and national economies, as well as intensifying business processes in the modern global environment is considered. It is emphasised that digital transformation takes place in various areas and directions, which allows entities of different levels of economic activity to successfully adapt to new challenges. It is found that the digital economy is not a separate economic unit at all, but a new economic model based on radically different technical and technological methods and social principles. The main directions of development of modern digital technologies in the world economy are demonstrated. An analysis of dynamic changes in the international ranking positions of Ukraine according to the indices of global and digital competitiveness is carried out. Based on a study of modern digitalisation processes in our country, it is proved that the IT industry is one of the leading sectors of the national economy. An analysis of exports of the domestic IT industry is carried out; the impact of exports of computer services and individual product groups on Ukraine’s GDP is estimated. As a result, it was found that the export of computer services has a strong impact on GDP. The priorities and general principles of ensuring the digitalisation of Ukraine’s economy are outlined, and the role of digitalisation in ensuring Ukraine’s economic growth is considered. The main directions of financing the digitalisation of Ukraine in accordance with the Digital Europe programme until 2027 are identified. It is emphasised that digitalisation processes are inherent in a kind of risks to which both society and business may not always be ready. The authors substantiate the guidelines for promoting the security of the main tools of the digital economy and emphasise that digital decision-making will be important for Ukraine’s post-war recovery.
ПРОБЛЕМИ І ПЕРСПЕКТИВИ РОЗВИТКУ ЦИФРОВІЗАЦІЇ: МІЖНАРОДНИЙ ТА НАЦІОНАЛЬНИЙ РІВЕНЬ
Keywords: digitalisation; digital economy; innovation; information and communication technologies